2013
DOI: 10.6061/clinics/2013(05)14
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ACE inhibition on endothelial progenitor cell mobilization and prognosis after acute myocardial infarction in type 2 diabetic patients

Abstract: OBJECTIVE:We aimed to assess the chemotactic response of endothelial progenitor cells to angiotensin-converting enzyme inhibitors in T2DM patients after acute myocardial infarction, as well as the associated prognosis.METHODS:Sixty-eight T2DM patients with acute myocardial infarction were randomized to either receive or not receive daily oral perindopril 4 mg, and 36 non-diabetic patients with acute myocardial infarction were enrolled as controls. The numbers of circulating CD45−/low+CD34+CD133+KDR+ endothelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 36 publications
0
12
0
3
Order By: Relevance
“…Some studies have demonstrated that subjects with cardiometabolic diseases present reduced baseline levels of CD34 + /VEGFR2 + cells [ 11 ] when compared with healthy controls. However, the current population with MetS is free of overt disease or pharmacological treatment, and these factors are known to alter the results [ 12 , 13 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have demonstrated that subjects with cardiometabolic diseases present reduced baseline levels of CD34 + /VEGFR2 + cells [ 11 ] when compared with healthy controls. However, the current population with MetS is free of overt disease or pharmacological treatment, and these factors are known to alter the results [ 12 , 13 , 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jialal et al [ 11 ] showed a reduced number of CACs along with impaired functionality in subjects with MetS, who were using antihypertensive drugs. However, some drugs, such as antihypertensives and statins, are already known to influence the number and/or functionality of CACs [ 12 , 13 ]. Thus, whether the number of CACs is already altered in drug naïve subjects with MetS is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that a low EPC level is an independent risk factor for future cardiovascular events such as unstable angina and myocardial infarction (MI) (7,8). MI (9) and limb ischemia (10,11) themselves have been associated with an increase in circulating EPC numbers, and vascular traumas such as acute MI with ST elevation (12) and percutaneous coronary intervention (13) have been suggested to induce the rapid mobilization of EPCs.…”
Section: Introductionmentioning
confidence: 99%
“…В исследовании Lin Ling и соавт. [19] оценивали динамику циркулирующих ЭПК и факторов, стимули-рующих мобилизацию ЭПК (VEGF и хемокинстромаль-ный фактор-1 (SDF-1α)) у больных с острым инфарктом миокарда (ОИМ). В группе пациентов с СД2 отмечалось снижение мобилизации и снижение пикового повыше-ния ЭПК по сравнению с пациентами без СД2, в то время как уровни VEGF и SDF-1α плазмы крови были выше в группе пациентов с СД2.…”
Section: сахарный диабет Diabetes Mellitusunclassified